The effects of prolactin receptor blockade in a murine endometriosis interna model - Christiane Otto; Hannes‐Friedrich Ulbrich; Christoph Freiberg (Wiley, 2022)
Abstract Endometriosis in an estrogen‐dependent disease that is characterized by the presence of endometrial tissue outside the uterine cavity leading to pain and infertility in many affected women. Highly efficient treatment options which create a hypo‐estrogenic environment can cause side effects such as hot flushes and bone mass loss that are not favorable for premenopausal women. Previous work has demonstrated that increased local or systemic prolactin seems to be involved in the pathogenesis of endometriosis. Here we examined two prolactin receptor (PRLR) blocking antibodies in a murine endometriosis interna model which relies on the induction of systemic hyperprolactinemia in female SHN mice. The severity of the disease is determined by the degree of endometrial invasion into the myometrium. In this model, endometriosis was inhibited by clinical gold standards such as progestins and anti‐estrogenic approaches. PRLR blockade completely inhibited endometriosis in this mouse model to the same extent as the anti‐estrogen faslodex or the GnRH antagonist cetrorelix. In contrast to cetrorelix and faslodex, the PRLR antibodies did not decrease relative uterine weights and were thus devoid of anti‐estrogenic effects. We therefore hypothesize that PRLR antibodies may present a novel and highly efficient treatment option for endometriosis with a good safety and tolerability profile. Clinical studies are on the way to test this hypothesis.